If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -12 + -23x = 6(-3x + -2) Reorder the terms: -12 + 5x + -23x = 6(-3x + -2) Combine like terms: 5x + -23x = -18x -12 + -18x = 6(-3x + -2) Reorder the terms: -12 + -18x = 6(-2 + -3x) -12 + -18x = (-2 * 6 + -3x * 6) -12 + -18x = (-12 + -18x) Add '12' to each side of the equation. -12 + 12 + -18x = -12 + 12 + -18x Combine like terms: -12 + 12 = 0 0 + -18x = -12 + 12 + -18x -18x = -12 + 12 + -18x Combine like terms: -12 + 12 = 0 -18x = 0 + -18x -18x = -18x Add '18x' to each side of the equation. -18x + 18x = -18x + 18x Combine like terms: -18x + 18x = 0 0 = -18x + 18x Combine like terms: -18x + 18x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 46-46x=(7x+3)(x-1) | | p=12x-5x | | 6-4x=4(1-x) | | 35-(2x-14)=40-(x+2) | | (2x^2)-x-(3)=0 | | 5x^2=23x+10 | | 40-7n=2(-5n+6)-n | | 8w/6+8=w-2 | | 12(4x-6)=8x+5(8x-6) | | 6s=-3T | | 5s=8t+12 | | 4(2x-1)-(-3x-5)=-179 | | 10b+5=76+5 | | 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 | | 5(x+8)-2x=60 | | 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 |